Eye health status and cause of visual impairment in survivors of Ebola virus disease in the Republic of Guinea: Etat de santé oculaire et cause de déficiences visuelles chez les survivants de la maladie à virus Ebola en République de Guinée - I, Fofana; TM, Bah; S, Diané; OA, Tonoheoua; AM, Ketema; B, Sovogui; F, Camara; L, Traoré; J, Traoré (Jour Med Resh and Health Sci, 2022)
Introduction : The Makona variant Ebola virus of the Zaire species, between its emergence in December 2013 and April 2016, caused an epidemic of unprecedented importance and severity in Guinea, with 3,814 cases notified, of which 3,358 were confirmed (88.0%) and 2,544 (66.7%) died. Our study aimed to assess the state of eye health and determine the causes of visual impairment in survivors of the Ebola virus disease epidemic in Guinea. Materiels ands methods : Multicenter cohort observational study involving all patients included in the PostEbogui study and who benefited from an ophthalmological consultation at the ophthalmology department of Nzérékoré or CADESSO. Results : In our series, we collected 26.02% (n = 108) of conjunctivitis; 11.32% (n = 47) sequelae of uveitis; 10.12% (n = 42) of cataract and 4.81% (n = 20) of glaucoma. There were 12.77% (n = 53) visual impairments and they were linked in 18 cases or 33.96% to the sequelae of uveitis. Discussion : The ophthalmological manifestations have been reported since the epidemics of 1976, but it was during the epidemics of 2014 that the descriptions of the ophthalmological complications were refined and here again, only during the convalescence phase while several months later some survivors still present eye problems. In our study, we recorded 12.77% (n = 53) visual impairment. The sequelae of uveitis were the main cause of visual impairment in our patients, with a frequency of 33.96% (n = 18).